An improved explicit integration algorithm with controllable numerical dissipation for structural dynamics - Yang, Chao; Wang, Xi; Li, Qiang; Xiao, Shoune (Archive of applied mechanics (1991), 2020)
In order to acquire efficient algorithms for complicated problems in structural dynamics, an improved integration algorithm with controllable numerical dissipation is developed based on a two-step explicit acceleration integration method. The improved method is a step-by-step integration scheme which is conditionally stable and robust in strongly nonlinear systems. The consistency, accuracy and the stability are analyzed for the improved method. Linear and nonlinear examples are employed to confirm the properties of the improved method. The results manifest that the improved method can be of second-order accuracy. It can be marginally stable in dynamic systems. The improved method possesses the property of energy conservation in conservative systems. Moreover, it is controllable for the numerical dissipation or algorithm damping which can be zero. The high-frequency oscillation can be effectively inhibited in a stiff problem. The spurious oscillation caused by the spatial discretization can be almost completely suppressed by the controllable numerical dissipation in a rod or a cantilever beam. It is applicable in transient and wave propagation problems.